Transplants and Indigenous Peoples: An Initial Approach - Rafael Fernandes, Estevão; Nóbrega Cavalcanti, Ana Karoline (Brazilian Journal of Transplantation, 2022)
This article indicates a set of issues related to transplants involving indigenous people. This is a topic not addressed in the literature of the country and for which it is relevant to take a closer look, given not only medical aspects, but also bioethical, socio cosmological, religious, social and cultural aspects. From an interdisciplinary perspective, we sought to draw attention to the importance of taking into account aspects related to the constitution of the indigenous person; implications regarding informed consent; and the need for a sensitive look at the intercultural differences involved. The conclusion was that it is necessary to form a protocol together with indigenous organizations and official bodies that consider cultural specificities. In addition, a survey of both institutional initiatives in other countries and the literature on the subject is still a task to be carried out in Brazil.